Sustainable business models and organisational resilience: a case study of Spier Wine Farm in South Africa - Van Staden, Kurt Martin (Rhodes University, Faculty of Commerce, Rhodes Business School)
The aim of the mini-thesis titled: "Sustainable Business Models and Organisational Resilience: A Case Study of Spier Wine Farm in South Africa" was to explore the relationship between sustainable business models and organisational resilience. Sustainability in wine makers extends beyond wine making techniques into other areas of the wine business to include hospitality, choice of glass and selecting suppliers of grapes. Spier Wine Farm, located outside the town of Stellenbosch in the Western Cape of South Africa, has been making wine since 1692. Spier has made a concerted effort in developing a sustainability strategy and introduction of sustainability into the business model. The South African wine industry is of importance to social and environmental sustainability in South Africa, creating over 270 000 jobs. Sustainability involves taking future generations into account when meeting the needs of the current generation, considering the triple bottom line of: environmental, social and economic value creation. The sustainable business model is thus an adaptation of a traditional business model to include creating and sustaining environmental and social value, in addition to traditional economic value. Resilience theory is centred around change in adaptive systems, focussing both on the role of change and the source of change. Making use of a deductive approach based on existing literature, a case study method allowed for an in-depth understanding of the relationship between sustainable business models and organisational resilience. Through semi-structured interviews and pattern matching data analysis, themes were identified. The research findings determined that a causal linkage between a sustainable business model and improved organisational resilience, in the South African context is likely to exist. The key themes that were considered to be contributing to this finding were: access to more sales markets, improved brand equity, reduced staff turnover and more efficient use of resources. An interdependence between sustainable business models and organisational resilience was found to likely not exist as a causal relationship between organisational resilience and sustainable business models was not found. The findings noted that sustainability was considered a contributing factor towards organisational resilience, but the relationship is not that of dependency as other ways to become resilient exist. Finally, it was recommended that adopting a sustainable business model is likely to lead to improved organisational resilience.
Keywords: Sustainable business model; Organizational resilience -- South Africa; Spier (Firm); Social responsibility of business -- South Africa -- Stellenbosch; Environmental responsibility -- South Africa -- Stellenbosch; Wine industry -- South Africa